Coupling of photocatalysis and catalysis using an optical fiber textile for room temperature depollution. (June 2022) - Molino, A.; Hamandi, M.; Grosjean, R.; Dappozze, F.; Lamaa, L.; Peruchon, L.; Brochier, C.; Dembélé, K.; El Hajem, M.; Vernoux, P.; Guillard, C.; Kaper, H.
Abstract: Herein, we investigate the interplay between a photocatalyst (TiO2 ) and a catalyst (Pt/TiO2 and Pt/CeO2 ) for the oxidation of formaldehyde and toluene at room temperature. A luminous textile is used as support and as light source for the photocatalyst. Our results indicate that the presence of the catalyst and the photocatalyst increases the catalytic performance for the oxidation of formaldehyde, while the photocatalytic performance for toluene oxidation decreases. The overall performance (toluene and formaldehyde degradation) of the system can be optimized with respect to the choice of support for the catalyst (e.g. TiO2 or CeO2 ), the quantity of Pt used, and the ratio between the catalyst and photocatalyst. In addition, different configurations of the photocatalyst and the catalyst on the textile are studied: under leaching and flow-through gas streams, catalyst and photocatalyst deposition on the same and opposite site of the textile are tested. The performance of the system can be optimized by adapting a configuration where the gas stream goes through the textile, while the deposition side of the catalyst and/or photocatalyst with respect to the gas stream is of minor importance. Graphical abstract: Schematic illustration of the degradation mechanism of volatile organic compounds (VOC) by coupling photocatalysis and catalysis using a luminous textile with optical fibers. Image 1 Highlights: Room temperature oxidation of toluene and formaldehyde. Coupling of photocatalyst and catalyst on an optical fiber textile enhances formaldehyde oxidation. Pt/CeO2 shows higher performance than Pt/TiO2 for catalytic formaldehyde oxidation at room temperature. Flow-through conditions are more effective than leaching gas streams.